Evaluasi Program Sistem Informasi Pengelolaan Keuangan Desa (Siskeudes) Studi Kasus Di Desa Seraras Kecamatan Sekadau Hilir Kabupaten Sekadau - Paskalis Alianto; Sri Maryuni; Pardi Pardi (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This research aims to evaluate the extent of the compliance level of Seraras Village government officials, Sekadau Regency, in using the Village Financial Management Information System (Siskeudes). The identified problems include the low technical and operational capabilities of village officials in carrying out village financial management tasks. This situation has led to the suboptimal implementation of the Siskeudes application and delays in the financial data input process beyond the established deadline. The research method used is a qualitative approach and a descriptive type of research, with data collection techniques obtained through interviews, observation, and documentation. The results show that the compliance level of village officials in using Siskeudes is still low, which is caused by limitations in Human Resources, lack of technical training, weak supervision, and low understanding of village financial management regulations. As a recommendation, this research suggests the need for improving human resource capacity and clear division of tasks through continuous training and technical guidance, enhancing coordination and supervision from the Regency Government, improving infrastructure, and strengthening periodic oversight and evaluation. Systematic periodic supervision and evaluation must be carried out by relevant agencies to ensure the effectiveness of implementing sanctions and rewards to encourage the compliance of village officials in running the financial management system accountably and on time.